2004
DOI: 10.1111/j.1440-1614.2004.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Safer at work: development and evaluation of an aggression and violence minimization program

Abstract: The program may contribute to helping health service industry staff attain a safer workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…However, according to Burns and Grove (1987) the response rate to mailed questionnaires is usually 25-30%, so the rate in this case is slightly better than is usually expected (Chapman et al, 2009). The findings of this study resonate strongly with those reported in other studies, suggesting that the consequences of WPV can be expected to be similar in other healthcare settings (Grenyer et al, 2004). These findings have implications for organizations, government and society at large.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, according to Burns and Grove (1987) the response rate to mailed questionnaires is usually 25-30%, so the rate in this case is slightly better than is usually expected (Chapman et al, 2009). The findings of this study resonate strongly with those reported in other studies, suggesting that the consequences of WPV can be expected to be similar in other healthcare settings (Grenyer et al, 2004). These findings have implications for organizations, government and society at large.…”
Section: Discussionsupporting
confidence: 82%
“…The literature shows that, similar to the participants in this study, nurses in many contexts and countries consider that being a recipient of WPV is inherent in the job and accepted as part of the nature of nursing (Grenyer et al, 2004). For example, 77% of the Minnesota nurses in Nachreiner et al's (2007) study expected assault as a consequence of their job.…”
Section: Consequences For Nursesmentioning
confidence: 83%
“…[1][2][3][4][5] There are a variety of contributing factors to workplace violence including patient/relative-related causes, organizational factors, healthcare staff issues, and societal facof violence ranging from verbal abuse to major assault. In addition, numerous studies report that nursing students, younger nurses, and less experienced and less educated nursing staff are more vulnerable to patient aggression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pressure caused by this unpredictability and by facing patients' violence contributes to increased workers' stress [12]. Patients' violence towards healthcare providers results from different factors, including severity of the disease, overcrowded wards and excessive waiting time [15,16,17,12]. Furthermore, the sequence of care in this type of ward is confusing for outpatients, who arrive in pain (medically justified or not), with an egocentric point of view, which cannot allow them to put their disease into perspective and compare their situation with that of the other patients [18], which is the task of the healthcare providers who receive them.…”
Section: Workloadmentioning
confidence: 99%